Heat mapping for district heating. (October 2018) - Brocklebank, Ian; Styring, Peter; Beck, Stephen
Abstract: If the UK wishes to decarbonise its energy supply, it should consider a wider uptake of district heating. Currently, district heating only accounts for 2% of the country's total heat supply. This paper considers the initial stages of designing a district heating network, the energy mapping in the local area, using a case study of Darley Dale, England. Energy mapping techniques are used to estimate the local area energy demand, a basis on which the district heating network design will rely on. The areas in the case study that are found to be profitable for possible district heating and where the rest of the district heating design work should focus on are Matlock, Bakewell and Darley Dale. The results of the mapping technique presented in this paper are found to agree with heat mapping work carried out by the UK Government. The agreement between the two mapping techniques shows that the mapping technique outlined in this paper is accurate enough for use.